2017
DOI: 10.1007/s11136-017-1651-0
|View full text |Cite
|
Sign up to set email alerts
|

The quality of life of older people aging in place: a literature review

Abstract: As no existing instrument assessing the quality of life of older people aging in place could be identified, such a tool should be developed, because any policy towards this growing group of people should be complemented by an evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
128
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 210 publications
(140 citation statements)
references
References 48 publications
4
128
0
8
Order By: Relevance
“…Ageing in place is an idea evolving in Western Europe according to which the elderly may maintain independence and self-reliance (HILLCOAT-NALLETAMBY et al 2010) by adapting their dwellings to the specific needs of older people (SCHARLACH 2017). The fact that such solutions are reasonable is corroborated by research on seniors' preferences, which shows that they want to live in their familiar environment as long as possible (VANLEERBERGHE et al 2017;GONYEA, BURNES 2013).…”
Section: Ageing In Placementioning
confidence: 86%
“…Ageing in place is an idea evolving in Western Europe according to which the elderly may maintain independence and self-reliance (HILLCOAT-NALLETAMBY et al 2010) by adapting their dwellings to the specific needs of older people (SCHARLACH 2017). The fact that such solutions are reasonable is corroborated by research on seniors' preferences, which shows that they want to live in their familiar environment as long as possible (VANLEERBERGHE et al 2017;GONYEA, BURNES 2013).…”
Section: Ageing In Placementioning
confidence: 86%
“…As important research relevant to the aging population, health-related quality of life (HRQOL) has been attracting increasing attention from domestic and foreign scholars in recent years [1][2][3][4]. The World Health Organization (WHO) defined HRQOL as an 'individual's perception of their position in life in the context of the culture and value system in which they live and in relation to their goals, expectations, standards and concerns' [5].…”
Section: Introductionmentioning
confidence: 99%
“…Assessing quality of life among older adults living at home has been criticized for being too focused on health-related factors and for not taking into account the complex factors that are important when living at home with declining health (Vanleerberghe, De Witte, Claes, Schalock, & Verté, 2017). For example, in a systematic review (Makai, Brouwer, Koopmanschap, Stolk, & Nieboer, 2014) found few quality of life and well-being instruments that included dimensions concerning environment.…”
Section: Introductionmentioning
confidence: 99%